Effect of Axial Vibration on Sliding Frictional Force between Shale and 45 Steel - Wu Hao; Chen Ping; Liu Yang; Ma Tianshou (Shock and Vibration)
Activating drill string vibration is an effective means to mitigate the excessive drag encountered during drilling complex-structure wells. However, the Coulomb model cannot describe the sliding friction behavior between drill string and borehole rock with imposed axial vibrations. To solve this problem, a specially designed experimental setup was utilized to investigate the characteristics of axial vibrating-sliding coupling friction. The results indicate that when vibration velocity is greater than sliding velocity, axial vibration can significantly reduce friction force between contact surfaces. Its friction reduction mechanism embodies not only the changes of instantaneous friction force, but also friction coefficient. Meanwhile, a friction coupling model was established based on the Hertz contact theory and Dahl model. The corresponding computational program was developed in Matlab/Simulink environment. The calculation results are in good agreement with the experimental results, verifying the validity of the present method. Furthermore, to overcome the shortcoming of Dahl model, a dynamic friction coefficient model was proposed to evaluate the friction-reducing effect of axial vibration using dimensional analysis method. The model parameters under different lubrication conditions were retrieved through inverse calculation with experimental data. This method provides a new solution for evaluating the friction-reducing effect of hydraulic oscillator and optimizing its placement.